2019
DOI: 10.1021/acsnano.9b00648
|View full text |Cite
|
Sign up to set email alerts
|

Assembly Reactions of Hepatitis B Capsid Protein into Capsid Nanoparticles Follow a Narrow Path through a Complex Reaction Landscape

Abstract: For many viruses, capsids (biological nanoparticles) assemble to protect genetic material and dissociate to release their cargo. To understand these contradictory properties, we analyzed capsid assembly for Hepatitis B virus; an endemic pathogen with an icosahedral, 120-homodimer capsid. We used solution X-ray scattering to examine trapped and equilibrated assembly reactions. To fit experimental results, we generated a library of unique intermediates, selected by umbrella sampling of Monte Carlo simulations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
144
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(154 citation statements)
references
References 96 publications
10
144
0
Order By: Relevance
“…Because equimolar assemblies proceed at similar apparent rates for both nanomaterials, it is possible that partial I53-40 structures transiently form in some non-stoichiometric regimes, but then (unlike I53-50) self-cure via disassembly and error correction prior to analysis. These results are consistent with previous analyses of in vitro virus capsid assembly, which suggest that relatively weak interfaces are required for cooperativity 23 , 33 , 50 , 54 . Furthermore, for HBV, a virus capsid architecture with thermodynamic properties similar to I53-40 and I53-50, contact energies and kinetic parameters which lead to cooperative assembly are constrained by the dual requirements of efficiency and fidelity 33 , 55 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Because equimolar assemblies proceed at similar apparent rates for both nanomaterials, it is possible that partial I53-40 structures transiently form in some non-stoichiometric regimes, but then (unlike I53-50) self-cure via disassembly and error correction prior to analysis. These results are consistent with previous analyses of in vitro virus capsid assembly, which suggest that relatively weak interfaces are required for cooperativity 23 , 33 , 50 , 54 . Furthermore, for HBV, a virus capsid architecture with thermodynamic properties similar to I53-40 and I53-50, contact energies and kinetic parameters which lead to cooperative assembly are constrained by the dual requirements of efficiency and fidelity 33 , 55 .…”
Section: Discussionsupporting
confidence: 92%
“…5a). Percent error minimization converged on ΔG con values of about 3.6 kcal/mol for I53-40 and 4.1 kcal/mol for I53-50, which, intriguingly, are similar to values previously observed for cooperatively assembling virus capsids 23,33,50,52 . Overlaying the experimental data onto the model shows that while the I53-40 data globally matches the model well, the I53-50 data deviate from the model in the regime where pentamer is super-stoichiometric ( Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…90 dimers [65]. What occurs between these two states, including the point(s) where the paths leading to T = 3 and T = 4 capsids diverge, has been obscure though progress is being made [66]. It has been reported that T = 3 capsids form early and briefly (seconds) whereas T = 4 capsids continue to be assembled for extended periods (hours), eventually becoming the majority species [67].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations that alter the assembly pathway can cause deep kinetic traps to reappear. Kinetic assembly pathways have been identified in HBV, by a combination of time-dependent small-angle X-ray scattering (SAXS) and umbrella Monte Carlo simulation with maximum entropy optimization 37 . Importantly, these kinetic assembly pathways appear only over narrow intervals of parameter space.…”
Section: Viral Self-assembly Dynamicsmentioning
confidence: 99%